Reproducibility assessment of magnetic resonance spectroscopy of pregenual anterior cingulate cortex across sessions and vendors via the cloud computing platform CloudBrain-MRS - Chen, Runhan; Lin, Meijin; Chen, Jianshu; Lin, Liangjie; Wang, Jiazheng; Li, Xiaoqing; Wang, Jianhua; Huang, Xu; Qian, Ling; Liu, Shaoxing; Long, Yuan; Guo, Di; et al. (NeuroImage (Orlando, Fla.), 2025)
•The reproducibility assessment of magnetic resonance spectroscopy was explored.•CV and ICC showed good reliability of within- and between- scanning sessions.•Bland-Altman plots indicated strong agreement in the repeated measurements.•Pearson correlation coefficients showed great reproducibility across three machines.•It revealed higher reproducibility for the intra-vendor than the inter-vendor. Proton magnetic resonance spectroscopy (1H-MRS) has potential in clinical diagnosis and understanding the mechanism of illnesses. However, its application is limited by the lack of standardization in data acquisition and processing across time points and between different magnetic resonance imaging (MRI) system vendors. This study examines whether metabolite concentrations obtained from different sessions, scanner models, and vendors can be reliably reproduced and combined for diagnostic analysis-an important consideration for rare disease research. Participants underwent magnetic resonance scanning once on two separate days within one week (one session per day, each including two 1H-MRS scans without subject movement) on each machine. Absolute metabolite concentrations were analyzed for reliability of within- and between- session using the coefficient of variation (CV), intraclass correlation coefficient (ICC) and Bland-Altman (BA) plot, and for reproducibility across the machines using the Pearson correlation coefficient. As for within- and between- session, most of the CV values for a group of all the first or second scans of a session, and from each session were below 20 %, and most of ICCs ranged from moderate (0.4≤ICC<0.59) to excellent (ICC≥0.75), which indicated high reliability. Most of the BA plots had the line of equality between 95 % confidence interval of bias (mean difference), therefore the differences over scanning time could be negligible. Majority of the Pearson correlation coefficients approached 1 with statistical significance (P < 0.001), showing high reproducibility across the three scanners. Additionally, the intra-vendor reproducibility was greater than the inter-vendor ones. [Display omitted]